Clinical Performance and Outcomes of an Injectable Bone Graft Substitute Following Core Decompression during the Treatment of Osteonecrosis of the Femoral Head - McConaghy, Kara; Louiselle, Erika L.; Knight, Ashley D.; Rullán, Pedro J.; Hortensius, Rebecca A.; Fitch, David A.; Piuzzi, Nicolas S. (The Journal of Hip Surgery, 2023)
Osteonecrosis of the femoral head (ONFH) can be challenging to manage, as it primarily affects younger adult patients. Hip preservation is preferred in this population, and there is a heightened focus on treatment strategies such as biologic adjuvants and bone grafting. Therefore, the objective of this systematic literature review was to evaluate the clinical performance of a commercially available injectable bone graft substitute (calcium sulfate [CaSO4]/calcium phosphate [CaPO4]; Pro-Dense, Wright Medical Technology Inc., Memphis, TN) following core decompression for the management of ONFH. Specifically, we aimed to examine (1) patient-reported outcomes, (2) progression of disease, (3) rate of revision, and (4) complications. A systematic literature review was performed in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analyses, using PubMed, Google Scholar, and Cochrane Library in July 2020 (gap search conducted in March 2022). The review included all clinical studies, published in English, on the use of an injectable bone graft substitute in ONFH-related procedures since 2007. Meta-analysis was conducted on Harris Hip Score (HHS), Visual Analog Scale (VAS), progression of disease, rate of revision, and complications. Nine studies were identified, with a total of 390 subjects ranging in age from 15 to 70 (weighted mean = 40.4) years old, with a weighted mean follow-up time of 37.1 months. Weighted mean improvement in HHS was +17.5 points (n = 296 procedures), while weighted mean improvement in VAS score was –3.0 points (n = 188 procedures). Overall weighted progression of disease for all patients was 6.1% (n = 17.9), including studies reporting precollapse (5.9%; n = 9.1/155) and/or postcollapse (9.91%; n = 16/162) lesions. Overall weighted revision rate was 2.9% (n = 11.5/390), including studies reporting precollapse (3.2%; n = 7.7/239) and/or postcollapse (4.3%; n = 8.2/191) lesions. The minor complication rate was 1.02% (n = 3/293), with no major complications reported. Clinical evidence on injectable CaSO4/CaPO4 bone graft substitute supports an acceptable benefit–risk profile, including safe real-world use since 2007, following core decompression for the treatment of ONFH.
Keywords: hip preservation; osteonecrosis of the femoral head; bone grafting; PRO-DENSE; outcomes